Antidiabetic Drugs in NAFLD: The Accomplishment of Two Goals at Once? - Matteo Tacelli; Ciro Celsa; Bianca Magro; Aurora Giannetti; Grazia Pennisi; Federica Spatola; Salvatore Petta (MDPI AG, 2018)
Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common cause of chronic liver disease in Western countries, accounting for 20⁻30% of general population and reaching a prevalence of 55% in patients with type 2 diabetes mellitus (T2DM). Insulin resistance plays a key role in pathogenic mechanisms of NAFLD. Many drugs have been tested but no medications have yet been approved. Antidiabetic drugs could have a role in the progression reduction of the disease. The aim of this review is to summarize evidence on efficacy and safety of antidiabetic drugs in patients with NAFLD. Metformin, a biguanide, is the most frequently used drug in the treatment of T2DM. To date 15 randomized controlled trials (RCTs) and four meta-analysis on the use of metformin in NAFLD are available. No significant improvement in histological liver fibrosis was shown, but it can be useful in the treatment of co-factors of NAFLD, like body weight, transaminase or cholesterol levels, and HbA1c levels. A possible protective role in various types of cancer has been reported for Metformin. Thiazolidinediones modulate insulin sensitivity by the activation of PPAR-γ. The RCTs and the meta-analysis available about the role of these drugs in NAFLD show an improvement in ballooning, lobular inflammation, and perhaps fibrosis, but some side effects, in particular cardiovascular, were showed. GLP-1 analogues stimulate insulin secretion by pancreatic beta cell and inhibit glucagon release; Liraglutide is the most used drug in this class and significantly improves steatosis, hepatocyte ballooning and transaminase levels. Scanty data about the role of DPP-4 and SGLT inhibitors were published. No data about insulin effects on NAFLD are available but it was showed a possible association between insulin use and the development of solid neoplasms, in particular HCC. In conclusion, antidiabetic drugs seem to be promising drugs, because they are able to treat both NAFLD manifestations and diabetes, preventing worsening of hepatic damage, but data are still conflicting. All antidiabetic drugs can be safely used in patients with compensated cirrhosis, while insulin is the preferred drug in decompensated Child C cirrhosis.